Comparative evaluation of tensile bond strength and microleakage of conventional glass ionomer cement, resin modified glass ionomer cement and compomer: An in vitro study - C Vishnu Rekha; Balagopal Varma; Jayanthi (Wolters Kluwer Medknow Publications, 2012)
Aim: The purpose of this study was to evaluate and compare the tensile bond strength and microleakage of Fuji IX GP, Fuji II LC, and compoglass and to compare bond strength with degree of microleakage exhibited by the same materials. Materials and Methods: Occlusal surfaces of 96 noncarious primary teeth were ground perpendicular to long axis of the tooth. Preparations were distributed into three groups consisting of Fuji IX GP, Fuji II LC and Compoglass. Specimens were tested for tensile bond strength by mounting them on Instron Universal Testing Machine. Ninety-six primary molars were treated with Fuji IX GP, Fuji II LC, and compoglass on box-only prepared proximal surface. Samples were thermocycled, stained with dye, sectioned, and scored for microleakage under stereomicroscope. ANOVA and Bonferrani correction test were done for comparisons. Pearson Chi-square test and regression analysis were done to assess the association between the parameters. Results: Compoglass showed highest tensile strength and Fuji II LC showed least microleakage. There was a significant difference between the three groups in tensile strength and microleakage levels. The correlation between tensile strength and microleakage level in each group showed that there was a significant negative correlation only in Group 3. Conclusion: Fuji II LC and compoglass can be advocated in primary teeth because of their superior physical properties when compared with Fuji IX GP.